Examining the Association Between Apparent Temperature and Mental Health-Related Emergency Room Visits in California. Issue 4 (11th August 2017) - Basu, Rupa; Gavin, Lyndsay; Pearson, Dharshani; Ebisu, Keita; Malig, Brian
Abstract: The association between ambient temperature and morbidity has been explored previously. However, the association between temperature and mental health-related outcomes, including violence and self-harm, remains relatively unexamined. For the period 2005–2013, we obtained daily counts of mental health-related emergency room visits involving injuries with an external cause for 16 California climate zones from the California Office of Statewide Health Planning and Development and combined them with data on mean apparent temperature, a combination of temperature and humidity. Using Poisson regression models, we estimated climate zone-level associations and then used random-effects meta-analyses to produce overall estimates. Analyses were stratified by season (warm: May–October; cold: November–April), race/ethnicity, and age. During the warm season, a 10°F (5.6°C) increase in same-day mean apparent temperature was associated with 4.8% (95% confidence interval (CI): 3.6, 6.0), 5.8% (95% CI: 4.5, 7.1), and 7.9% (95% CI: 7.3, 8.4) increases in the risk of emergency room visits for mental health disorders, self-injury/suicide, and intentional injury/homicide, respectively. High temperatures during the cold season were also positively associated with these outcomes. Variations were observed by race/ethnicity, age group, and sex, with Hispanics, whites, persons aged 6–18 years, and females being at greatest risk for most outcomes. Increasing mean apparent temperature was found to have acute associations with mental health outcomes and intentional injuries, and these findings warrant further study in other locations.